Intimate Partner Violence Victimization and Perpetration in a Turkish Female Sample: Rejection Sensitivity and Hostility - Kahya, Yasemin (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) against women is one of the most alarming social problems all over the world. Recently, IPV research focuses on the bidirectional nature of the phenomenon, which underlines that both women and men can equally be victims and perpetrators of IPV, especially in community samples. The cycle of violence theory asserts that child abuse and neglect (CAN) is a vulnerability factor for being both a victim and perpetrator of IPV while developmental mechanisms perspective assesses mediators explaining this association. The purpose of the current study was to investigate whether CAN and each type of CAN (emotional maltreatment, physical abuse and neglect, and sexual abuse) would be associated with victimization of and perpetration by women via the multiple mediator roles of rejection sensitivity and hostility after controlling for co-occurring CAN types. The sample (N = 288) included Turkish women who were currently married or in a romantic relationship or in one of these statutes in the past year. Participants were recruited via online survey to fill out the related questionnaires. The results of Bootstrap analyses showed that the total CAN scores were associated with being a victim and perpetrator of IPV in the past year. Rejection sensitivity mediated the association between CAN and being a victim of IPV while hostility was a mediator between CAN and perpetration of IPV. Childhood emotional maltreatment (CEM) was the only trauma type which predicted victimization by rejection sensitivity and perpetration by hostility above and beyond the effects of co-occurring trauma types. The present study findings contributed to the growing literature that women exposed to childhood traumas can also be perpetrators of violence that was a demonstrated risk factor for the repeated victimization. Results implied that developmental and process variables should be taken into account rather than a strict gendered analysis of IPV in research and clinical practice.